Web Usage Mining, Pattern Discovery dan Log File - Suratno, Tri; Prahasto, Toni; Rochim, Adian Fatchur (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Analysis  of  data  to  access  the  server  can  provide  significant  and  useful  information  for  performance  improvement,  restructuring  andimproving the effectiveness of a web site. Data mining is one of the most effective way to detect a series of patterns of information from large amounts of data. Application of  data mining  on  Internet use  called web  mining  is a set of  data mining  techniques  are  used  for the web. Web mining technologies and data mining is a combination of web, which is the integration of technology resources extracted from the  information  world wide web  as  the  implications  of the  web  resources  of interest to  know the  value  of the  model extraction Potentialuse of  data mining  algorithms  over  a variety  of  observational  data for  identify  patterns  of  web resources. Target analysis of web mining is the data from the web, such as data visitors access, web page structure, and format web pages.  Target analysis of the study is that web mining  web  usage  mining  using  association  rules  on  the  website  www.faperta.unja.ac.id  obtained  from  the  log  file  that  is  used  to discover the navigation patterns, and discover the rules of the association between a combination of items.  To  determine the pattern ofvisits  in  a  web,  and  to  identify  what  pages  are frequented by  visitors  of  a  website,  which  can  be used  to  improve  website design  andrecommend the display, as well as the links are often used by visitors, so the quality of services from website www.faperta.unja.ac.id can be provided effectively and efficiently.Keywords : Web Mining; Web usage mining; Data mining; Log file; Website; World wide web